Implementasi kurikulum berbasis cinta pada pembelajaran akidah akhlak di Madrasah Aliyah Negeri 1 Mandailing Natal - Nst, Puli Taslim; Al-Husna, Khofifah Indah (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
This study aims to describe the implementation of a love-based curriculum in Aqidah Akhlak learning at Madrasah Aliyah Negeri 1 Mandailing Natal and to examine its impact on pedagogical relationships, learning motivation, and students’ character formation. A qualitative case study approach was employed to explore classroom practices through interviews, observations, and document analysis. The findings indicate that the love-based curriculum is implemented through integrative learning strategies emphasizing role modeling, dialogical communication, and the internalization of compassion values. This approach contributes to a more humanistic classroom atmosphere, increased learning motivation, and the development of empathy, responsibility, and discipline among students. However, several challenges remain, including limited teacher understanding, insufficient training, and inadequate supporting facilities. These findings suggest that the love-based curriculum holds significant potential as a transformative approach for strengthening Aqidah Akhlak learning and fostering holistic character development in Islamic educational contexts.